Engineering and Process of Investment Casting for Pump Impellers - Agus Edy Pramono; Arif Dermawan (Recent in Engineering Science and Technology, 2023)
This article explains the pump impeller fabrication process using the investment casting method as an alternative to sand casting. The process aims to achieve precise dimensions, thereby reducing the need for additional machining processes. The process begins with creating a metal pattern. The metal pattern is conducted through machining with dimensional additions. The dimensions are determined by summing up the dimensional sizes, considering SS316L material shrinkage (2.5~3.5%), wax shrinkage (1%), and machining (5mm). The further process is wax injection to create wax patterns, the making of gating system, and ceramic sintering molding. The wax patterns are made separately for each part of the impeller, and then assembled into a complete wax pattern that matches the impeller's geometry and includes the gating system. The wax patterns undergo repeated dipping into slurry and stucco solutions, forming a thick ceramic layer around the wax impeller patterns. After melting the wax from the ceramic mold, cavities are left according to the impeller's geometry. Sintering the ceramic mold impeller at 1000°C forms a hard ceramic mold with cavities ready to receive the molten metal. Once the molten metal solidifies and is removed from the ceramic mold, the casting impeller is ready for further machining processes.